Real‐world evidence in a national health service: results of the UK CardioMEMS HF System Post‐Market Study. (9th December 2021) - Cowie, Martin R.; Flett, Andrew; Cowburn, Peter; Foley, Paul; Chandrasekaran, Badrinathan; Loke, Ian; Critoph, Chris; Gardner, Roy S.; Guha, Kaushik; Betts, Tim R.; Carr‐White, Gerry; Zaidi, Amir; et al.
Abstract: Aims: The CardioMEMS HF System Post‐Market Study (COAST) was designed to evaluate the safety, effectiveness, and feasibility of haemodynamic‐guided heart failure (HF) management using a small sensor implanted in the pulmonary artery of New York Heart Association (NYHA) Class III HF patients in the UK, Europe, and Australia. Methods and results: COAST is a prospective, international, multicentre, open‐label clinical study (NCT02954341). The primary clinical endpoint compares annualized HF hospitalization rates after 1 year of haemodynamic‐guided management vs. the year prior to sensor implantation in patients with NYHA Class III symptoms and a previous HF hospitalization. The primary safety endpoints assess freedom from device/system‐related complications and pressure sensor failure after 2 years. Results from the first 100 patients implanted at 14 out of the 15 participating centres in the UK are reported here. At baseline, all patients were in NYHA Class III, 70% were male, mean age was 69 ± 12 years, and 39% had an aetiology of ischaemic cardiomyopathy. The annualized HF hospitalization rate after 12 months was 82% lower [95% confidence interval 72–88%] than the previous 12 months (0.27 vs. 1.52 events/patient‐year, respectively, P < 0.0001). Freedom from device/system‐related complications and pressure sensor failure at 2 years was 100% and 99%, respectively. Conclusions: Remote haemodynamic‐guided HF management, using frequent assessment of pulmonary artery pressures, was successfully implemented at 14 specialist centres in the UK. Haemodynamic‐guided HF management was safe and significantly reduced hospitalization in a group of high‐risk patients. These results support implementation of this innovative remote management strategy to improve outcome for patients with symptomatic HF. Clinical registration number: ClinicalTrials.gov identifier: NCT02954341.